2019
DOI: 10.1200/jop.18.00703
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Adverse Events Requiring Hospitalization: Spectrum of Toxicity, Treatment, and Outcomes

Abstract: PURPOSE: Immune checkpoint inhibitors (ICIs) cause immune-related adverse events (irAEs). The proportion of patients who are hospitalized for irAEs and their spectrum, management, and outcomes are not well described. METHODS: We report the proportion of hospitalized patients in an academic center who were treated with ICIs from May to December 2017. Patient characteristics, toxicities, management, and outcomes for confirmed irAE admissions are reported. Associations between patient features and irAE hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
33
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 34 publications
6
33
3
2
Order By: Relevance
“…Our study showed that the absolute incidence of irAEs requiring hospitalization in the study population increased over time from 2011 to 2019, a finding that is consistent with the increased use of ICI over that time period. We demonstrate that combination therapy is associated with increased odds of irAE requiring hospitalization, which is in agreement with prior findings that combination therapy 32 and CTLA-4 therapy 23 33–35 are associated with higher incidence of irAEs relative to PD-1 or PD-L1 treatment. The incidence of irAEs requiring hospitalization in this study was 3.5% overall, with 3.3% for patients receiving PD-1, 1.1% for patients receiving PD-L1, 3.9% for patients receiving CTLA-4 therapy, and 7.3% for patients on combination therapy.…”
Section: Discussion/conclusionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed that the absolute incidence of irAEs requiring hospitalization in the study population increased over time from 2011 to 2019, a finding that is consistent with the increased use of ICI over that time period. We demonstrate that combination therapy is associated with increased odds of irAE requiring hospitalization, which is in agreement with prior findings that combination therapy 32 and CTLA-4 therapy 23 33–35 are associated with higher incidence of irAEs relative to PD-1 or PD-L1 treatment. The incidence of irAEs requiring hospitalization in this study was 3.5% overall, with 3.3% for patients receiving PD-1, 1.1% for patients receiving PD-L1, 3.9% for patients receiving CTLA-4 therapy, and 7.3% for patients on combination therapy.…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…In our study, average hospitalization length of stay for irAE patients was 6 days, which is consistent with previous study results. 32 Our study reports that patients with severe irAEs were more likely to have an ICU admission (OR 2.60, p<0.001), which is not a widely reported outcome in large scale ICI studies. 34 …”
Section: Discussion/conclusionmentioning
confidence: 59%
“…In investigating risk factors for irAE hospitalization, we found that CTLA‐4 therapy or combination ICI therapy was associated with a nearly twofold increase in irAE admission risk relative to PD‐1/PD‐L1 therapy. This is consistent with previous findings that combination ICI therapy is a risk factor for the occurrence of severe or life‐threatening irAEs, often requiring hospitalization [18, 19]. Furthermore, patients with severe toxicities caused by CTLA‐4 therapy and CTLA‐4 plus PD‐1 combination therapy were admitted significantly earlier in treatment (at 6 to 7 weeks) than those caused by PD‐1/PD‐L1 monotherapy (at 3 months).…”
Section: Discussionsupporting
confidence: 91%
“…12 Although information regarding the development of immune-related adverse events (irAEs) in the SEER analysis by Youn et al 2 was limited, recent data have suggested that patient age >65 years may be a risk factor for the development of irAEs and may potentially increase the risk of hospitalization after receipt of immunotherapy. 13 Munchnik et al 7 reported that a disproportionate number of older patients required medical interventions to manage their irAEs compared with what was observed in previous clinical trials, along with a higher rate of treatment discontinuation. These findings highlight the inherent vulnerability of older adults and have significant implications with respect to cost-effectiveness and treatment decision making, which ultimately should be factored into the informed consent process.…”
mentioning
confidence: 97%
“…This finding is concordant with recent reports demonstrating that immune checkpoint inhibitors can be administered with caution in patients who have autoimmune conditions . Although information regarding the development of immune‐related adverse events (irAEs) in the SEER analysis by Youn et al was limited, recent data have suggested that patient age >65 years may be a risk factor for the development of irAEs and may potentially increase the risk of hospitalization after receipt of immunotherapy . Munchnik et al reported that a disproportionate number of older patients required medical interventions to manage their irAEs compared with what was observed in previous clinical trials, along with a higher rate of treatment discontinuation.…”
mentioning
confidence: 99%